Understanding but unhelpful: Do grateful people value responsiveness or perceived benefit when receiving help? - LIM, Elizabeth (Institutional Knowledge at Singapore Management University, 2021)
Two studies examined the links between the grateful disposition, cognitive appraisals (perceived value and perceived responsiveness), state gratitude, and affiliative intentions (one’s desire to build or maintain relationships with his/her benefactor). In Study 1, 248 participants went through a guided scenario task where they recalled help experiences that were helpful and not so helpful. Dispositional gratitude predicted perceived value and perceived responsiveness (H1A and H1B). These cognitive appraisals in turn predicted state gratitude (H2 and H3). Finally, state gratitude predicted affiliative intentions (H4). Supporting H5A and H5B, cognitive appraisals and state gratitude mediated the link between dispositional gratitude and affiliative intentions. Study 2 tested whether grateful individuals place more weight on perceived value versus perceived responsiveness in their desire to affiliate with a helper (H6 and H7). Nine hundred sixty-eight participants were randomly assigned to read a vignette in which they received help from a colleague who was either low versus high on responsiveness. The help they received was either good (high value) or bad (low value). Dispositional gratitude did not interact with either manipulated responsiveness or manipulated value failing to support H6 and H7. However, exploratory analyses using participants’ ratings of perceived responsiveness and value provided partial support for the hypotheses. Perceived value had a positive effect on the desire to affiliate for both grateful individuals and ingrates when responsiveness was low (supporting H7) and when responsiveness was high. Although H6 predicted that dispositionally grateful individuals would desire to affiliate with highly responsive helpers regardless of the value of help, whereas ingrates would place more weight on value—the predicted interaction was not obtained. Nevertheless, results support the notion that cognitive appraisals play an instrumental role in the experience of gratitude as well as social motivations such as affiliative intentions.